Enhanced stability of ZnTPPS by polymeric gold nanoparticles in acidic aqueous solutions. Issue 5 (3rd May 2016) - Chai, Zhihua; Ma, Liya; Wang, Yanxia; Ren, Xuejun; Gao, Ming
ABSTRACT: Novel kind of core-shell corona complex micelles were prepared, which enhanced both the hydrolytic stability and the photostability of water-soluble zinc tetrakis(4-sulfonatophenyl) porphyrin (ZnTPPS) in acidic aqueous solutions. The core-shell gold nanoparticles (AuNPS) were synthesized by reducing HAuCl4 and di-thioester terminated block copolymer, poly(Nisopropylacrylamide)- block -poly(4-vinylpyridine) (PNIPAM- b -P4VP). The complex micelles with gold core, P4VP/ZnTPPS shell and PNIPAM corona were formed by simple mixing of gold nanoparticles and ZnTPPS. The photochemical properties of the complex micelles were studied by UV–Visiblespectroscopy and fluorescence spectroscopy. The results showed trapping of ZnTPPS in the positively charged micellar shell that effectively prevented demetallation of the ZnTPPS that would occur in acidic aqueous solutions. Furthermore, with appropriate concentration of gold nanoparticles, ZnTPPS in the complex micelle had excellent photostability by suppression of generation of reactive oxygen species (ROS). The enhanced stability of ZnTPPS in acidic aqueous media could be extensively used for photocatalysis and in solar cells.